Proteomic insights into extinction memory deficits in stress-susceptible female rats - Irizarry-Méndez, Nashaly; Acosta-Pierantoni, Yelitza; Diaz-Vazquez, Alondra; Hernández, Anixa; Colón, Maria; Tosado-Rodríguez, Eduardo L.; Cantres-Rosario, Yadira M.; Roche-Lima, Abiel; Rodríguez-De Jesús, Ana E.; Meléndez, Loyda M.; Porter, James T. (Frontiers in Behavioral Neuroscience, 2026)
Stress exposure can disrupt fear extinction, which is a hallmark of some stress-related disorders. The underlying molecular mechanisms of impaired extinction, especially in females, remain poorly understood. In this study, we investigated proteomics changes in the infralimbic cortex, a region critical for fear suppression, in female rats exposed to single prolonged stress (SPS). One week after SPS exposure, adult female rats underwent auditory fear conditioning and extinction training and were classified as susceptible or resilient based on their extinction performance. Quantitative proteomics using tandem mass tag labeling combined with bioinformatics analysis identified distinct proteins and pathways differentiating the groups. Susceptible rats displayed unique proteomic profiles in the infralimbic cortex. Several of the 53 differentially expressed proteins are associated with synaptic plasticity and memory, including neurogranin and microtubule-associated protein tau (MAPT). Pathway enrichment analysis identified alterations in synaptogenesis, clathrin-mediated endocytosis, calcium signaling, and chaperone-mediated autophagy. Functional validation using AAV-shRNA knockdown of neurogranin or MAPT in CAMKIIα-expressing neurons of the infralimbic cortex improved extinction memory in SPS-exposed animals. Our findings suggest that dysregulated protein expression in the infralimbic cortex contributes to impaired extinction memory and traumatic stress susceptibility in female rats, offering insight into the neurobiological mechanisms underlying vulnerability to stress-related disorders.